« Paroles de flics ». Communications policières et actualité politique au Maroc (2005-2023) - Mériam Cheikh (L’Année du Maghreb)
In February 2005, an unusual press publication in Morocco appeared amid the profusion of titles (dailies, weeklies and monthlies) that had been appearing in Arabic and French on the newsstands of the country’s major cities since the 1990s. One of these is the new police journal, entitled Police Magazine, which has been heralded with great fanfare as a move away from the traditional institutional publications that have existed until now and which were not always aimed at the general public. Driven by a strong desire to address the general public directly in Arabic and French, the magazine’s editors - who happen to be in positions of responsibility within the police force - aim to reconcile their security service, which suffers from a bad reputation, and to seize upon the new vulgate on political liberalisation and the democratisation process. Aware that they are, theoretically speaking, a key player in the protection and enforcement of human rights, the Moroccan police, while still discredited for the violations of which they became notorious during the so-called years of lead, and which were addressed in the debates led by the Equity and Reconciliation Commission (Instance équité et réconciliation - IER), are now asserting their attachment to these ideals as the IER’s work draws to a close. The resurgence of police publishing (in Arabic and French) will mark the first milestone in the establishment of a system of communication that will be visible to all and which, over the course of the last two decades (2005-2023), will gradually become a fully-fledged professional service responsible, for the first time, not for denying but for addressing through discourse the strong tension between police action and civil liberties. To this end, and in the context of police reform and managerial rationalisation of its workforce, the Police Department will be showcasing its work each month, the diversity of its services (Public Security in charge of crime, Criminal Investigation Department in charge of criminal investigations, General Intelligence, Border Police in charge of migratory flows to Europe and Law Enforcement) and the ways in which it defines these services. These not only show how the police are organised from the inside but also what their new priorities are, with urban and juvenile delinquency at the top of the list.By examining two decades of a publication known as “Police Magazine” from 2005 to 2013, then “Revue de Police” from 2014 to the present day, this article will look at how the security forces engage in institutional communication aimed at the Moroccan public, and what forms this takes according to different political shifts, ranging from political openness to political closedness. Without going into the details of the 101 issues of Police Magazine and Revue de Police under review (the space available does not allow for text analysis), the aim is to highlight the most significant elements that demonstrate the stages of opening up and then of closing down of the police’s discourse on itself. In the first section, we provide a brief history of the development of police imagery in Morocco, from independence in 1956 to the end of the 1990s, the time of the political transition that was supposed to mark the beginning of what some analysts have hastily termed “the democratic transition”, In the second part, we look at how the police represent themselves by opting for a form of writing that is more journalistic than communication-based, giving the impression that they are trying to tell the truth about themselves by using the language of the regime’s “new era”: namely that of human and social development. The final section is devoted to the shaping of the police profession as the profession of police communicator becomes more refined. In line with the political readjustment period, communication will become less and less aimed at the general public and more and more focused on members of the security forces.